Komitmen Organisasi Memoderasi Pengaruh Pengendalian Intern, Kualitas Sumber Daya Manusia, dan Pemanfaatan Teknologi Informasi pada Kualitas Laporan Keuangan - Satriawan, Gusti Made Indra; Dewi, Gusti Ayu Ketut Rencana Sari (Universitas Pendidikan Ganesha, 2020)
The aimed of this study was to review and prove the effect of the internal control, the quality of human resources, and the application of information technologhy on the quality of financial report with the organization commitment as moderating agent. The indicator used to measure were relevancy, reliability, understandibility, and comparability. The total number of the respondents were 116 that was diffused into 29 of Regional Apparatus Organization in Buleleng Regency by determining the criteria of the respondent.Â Analysis technique used was analisis multiple linear regression and MRA. The results were revealed internal control and the quality of human resources were effecting, while the application of information technology was not effecting, and the organization commitment could strengthen internal control, but could not strengthen the quality of human resources and the application of information technology on the quality of financial report.Â